Body memory, metaphor and movement - Koch, Sabine C.; Fuchs, Thomas (Advances in consciousness research (AiCR) 1381-589X, 2012)
Body Memory, Metaphor and Movement is an interdisciplinary volume with contributions from philosophers, cognitive scientists, and movement therapists. Part one provides the phenomenologically grounded definition of body memory with its different typologies. Part two follows the aim to integrate phenomenology, conceptual metaphor theory, and embodiment approaches from the cognitive sciences for the development of appropriate empirical methods to address body memory. Part three inquires into the forms and effects of therapeutic work with body memory, based on the integration of theory, empirical